2019
DOI: 10.3906/sag-1808-168
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability study of the Turkish version of the Hand20 questionnaire

Abstract: Background/aim: This study aimed to translate and validate the Turkish version of the Hand20 questionnaire. Materials and methods:Patients who had upper extremity involvement and stable symptoms for the previous 4 weeks in their upper extremities were included in the study. Patients who were illiterate or used a splint during the day were excluded from the study. Participants completed the Turkish version of the Disabilities of the Arm, Shoulder, and Hand (DASH-T) questionnaire once and the final version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The reason for this may be due to gender differences in the distribution of household chores within Turkey. Similarly, in the Turkish version study of Hand20, the researchers stated that most male patients did not answer questions such as those mentioned above (Tore & Oskay, 2019). Tore and Oskay (2019) also determined that participants between 15 and 80 years of age could easily complete the Hand20.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason for this may be due to gender differences in the distribution of household chores within Turkey. Similarly, in the Turkish version study of Hand20, the researchers stated that most male patients did not answer questions such as those mentioned above (Tore & Oskay, 2019). Tore and Oskay (2019) also determined that participants between 15 and 80 years of age could easily complete the Hand20.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the Turkish version study of Hand20, the researchers stated that most male patients did not answer questions such as those mentioned above (Tore & Oskay, 2019). Tore and Oskay (2019) also determined that participants between 15 and 80 years of age could easily complete the Hand20. The current study also found that participants between 8 and 79 years of age had no difficulties in completing the Turkish version of the JHand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations